Modulation-assisted machining of compacted graphite iron with coated carbide tool in dry condition. (September 2022) - Sandoval, Juan; Ali, Aaqib; Kwon, Patrick; Guo, Yang
Abstract: Compacted graphite iron (CGI) is a new material replacing conventional gray cast iron (FGI) for diesel engine block applications due to its superior mechanical properties. However, widespread adoption of CGI is hindered by its poor machinability, which is reflected by the rapid tool wear especially at higher cutting speeds. In current industrial practice, CGI is usually machined with coated carbide tools at low to medium speeds (< 200 m/min). This study investigates the effect of modulation-assisted machining (MAM) on tool wear in dry turning of CGI with coated carbide tool. A new MAM turning setup is implemented for conducting the longitudinal turning experiments. Tool wear, cutting forces and tool temperature are characterized for both conventional machining (CM) turning and MAM turning at three cutting speeds: 150, 250 and 350 m/min. The results show wear reduction by MAM is not significant at the low cutting speed (150 m/min), but it is quite significant at the higher cutting speeds (250 and 350 m/min). The cutting force and temperature results can be well correlated with the wear results, revealing the dependency of the forces and temperature on the tool wear and the severity of iron adhesion. This study demonstrates the potential of MAM in enhancing the productivity of machining CGI with the coated carbide tool. The results are also useful for better understanding the wear mechanism in cutting CGI with the coated carbide tool.